THE EFFECT OF INFORMATION AND TECHNOLOGY BASED ENGKLEK CARD LEARNING MEDIA ON ELEMENTARY SCHOOL STUDENTS LEARNING OUTCOMES IN EDUCATION AND CITIZENSHIP SUBJECTS - Laela Ferani; Rita Kusumah (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2025)
The presence of increasingly sophisticated technology has caused the current generation to ignore and abandon the cultural values ​​inherited from previous generations. Young people are no longer familiar with traditional games. They are more interested in playing modern games, namely online games. This study aims to determine the effect of using IT-based engklek card learning media on the learning outcomes of fourth-grade students in Civics at SDN 2 Koreak, Cigandamekar District, Kuningan Regency. This study used a quantitative research design with a pre-experimental one-group pretest-posttest and a test as the research instrument. The research data were analyzed descriptively and inferentially using a t-test. Based on the data obtained from the t-test, the significance value is greater than 0.05, so it can be concluded that there is a significant effect of the use of IT-based engklek card learning media on student learning outcomes. The average pre-test obtained before treatment was given was 52. After the action was carried out using IT-based card-based hopscotch learning media, the average post-test score was 69. It can be concluded that the use of IT-based card-based hopscotch learning media applied to the Civics subject has an effect on student learning outcomes.